PENGARUH KEPEMIMPINAN TANSFORMASIONAL DAN KOMITMEN ORGANISASI TERHADAP PRESTASI KERJA KARYAWAN PADA PT.BANK SULUT (KANTOR PUSAT) - WEWENGKANG, CINDY CLAUDIA; Roring, Mieke; Pio, Riane (Sam Ratulangi University, 2014)
Abstract : Empowerment of human resources in the company right will result in an increase thecompany's ability to obtain and retain the best people in the field. Utilization of human resourcesmanagement right can also motivate each individual to perform the work in accordance with companyobjectives. No matter how modern technology is used, or how much money it is prepared, but without ahuman resources professional it all becomes meaningless.This study aims to determine whether Transformational Leadership and OrganizationalCommitment to Achievement employees working at PT Bank Sulawesi (Central Office). This study used aquantitative approach. The main variable in this study is Transformational Leadership OrganizationalCommitment and Employee Job Performance.In this study population of 252 respondents PT. Bank of North Sulawesi with a sample of 45employees. From the results of the data obtained through questionnaires and calculated with SPSS 19using the multiple correlation analysis and multiple regression has obtained significant data. Afteranalyzing the correlation and regression methods were then tested with hypothesis testing, in this case thehypothesis testing using t-test testing. In testing the t test assumed in transformational leadershipvariable count T <T table is -0.333 <1.682 on the variable X1, it can be concluded can not reject Ho. While onthe Organizational Commitment X2 reject Ho T count> T able and accept H 1 when T count <T able. Upon gettingthe T count tested significantly with Ttable for error level 5% test of 1,682. So based on the count T = 5.925 andT = table count 1,682maka T> T table = 5.925> 1.682.The results of calculation between Transformational Leadership and Organizational CommitmentAgainst Employee Job Performance with regression analysis showed that the TransformationalLeadership and Organizational Commitment influential Against Employee Job Performance In NorthSulawesi PT Bank (Central Office).Keywords: Transformational Leadership, Organizational Commitment, Employee Job Performance